АНАЛІЗ ПЕРЕХІДНИХ ПРОЦЕСІВ У КОЛАХ ЕЛЕКТРОРОЗРЯДНИХ УСТАНОВОК ЗІ ЗВОРОТНИМ ЗВ'ЯЗКОМ ЗА НАПРУГОЮ З УРАХУВАННЯМ ЧАСУ ВІДНОВЛЕННЯ ЗАМИКАЮЧИХ ВЛАСТИВОСТЕЙ ЇХНІХ НАПІВПРОВІДНИКОВИХ КОМУТАТОРІВ - Щерба, А.А.; Супруновська, Н.І.; Щерба, М.А. (Інститут електродинаміки НАН України, Київ, 2018)
The paper substantiates the approach to the selection of the inductance value of the choke in the reverse-recharge circuit of a capacitor of thyristor electric discharge installations with controlled voltage feedback (in particular, installations for volumetric electro-spark dispersion of metals in a liquid). The approach is based on taking into account the recovery time of the locking properties of the thyristor in the discharge circuit of such installations, as well as the permissible losses in the reverse-recharge circuit of a capacitor. The results of mathematical modeling of the transient processes in the capacitor circuits of such installations have shown that if the choke inductance is correctly selected in the reverse-recharge circuit of a capacitor, then it is possible to switch on this circuit before the end of the discharge process of the capacitor to the load (i.e., when the capacitor discharge circuit change its configuration during capacitor discharge).In this case, the losses in the reverse-recharge of the capacitor will not exceed 10% of the energy stored in the capacitor before the recharge start. References 10, figures 5, tables 2.